2018
DOI: 10.14505//jemt.v9.4(28).02
|View full text |Cite
|
Sign up to set email alerts
|

How Country Image Affects Intention to Visit a Destination: Evidence from Russian Tourists Visiting Switzerland

Abstract: The paper examines how country image affects the intention to visit a destination by means of a quantitative study conducted in Russia. It specifically explores the mediating influence of psychological destination image, functional destination image, and attitude towards the destination between country image and visiting intention. Data for the research were collected from a survey involving 919 respondents in Russia who had gone on a vacation, at least, once in the past 12 months. A series of mediation models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similarly, it has been discovered that there is a positive correlation between the perception of a destination and the intention to visit a destination, which contributes significantly to tourists' intention to visit tourism destinations (Chaulagain, Wiitala & Fu, 2019;Ponnapureddy, Wagenseil, Belozerova & Mirzoian, 2018;Satyarini, Rahmanita & Setarnawat, 2017). Foroudi, Akarsu, Ageeva, Foroudi, Dennis, and Melewar (2018) concluded that the intention of tourists to visit a tourism destination is based on their perceived image of the destination.…”
Section: Intentions To Visit and Destination Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been discovered that there is a positive correlation between the perception of a destination and the intention to visit a destination, which contributes significantly to tourists' intention to visit tourism destinations (Chaulagain, Wiitala & Fu, 2019;Ponnapureddy, Wagenseil, Belozerova & Mirzoian, 2018;Satyarini, Rahmanita & Setarnawat, 2017). Foroudi, Akarsu, Ageeva, Foroudi, Dennis, and Melewar (2018) concluded that the intention of tourists to visit a tourism destination is based on their perceived image of the destination.…”
Section: Intentions To Visit and Destination Imagementioning
confidence: 99%
“…Satyarini et al (2017) encouraged the building of a positive brand, through improving communication skills and partnership between government officials, locals and the local government to enhance the natural environment and project a positive destination image to the tourists. The result from the study conducted in Switzerland by Ponnapureddy et al (2018) suggested the inclusion of destination image into the message contents during marketing or awareness campaigns. As a result, the image of a product or service is a significant consideration when choosing a product, service, location, or person.…”
Section: Intentions To Visit and Destination Imagementioning
confidence: 99%